An expert system to control construction problem in rigid highway pavement - Mohamad Fathi Bin Mohamad Radzuan (School of Environmental Engineering, University Malaysia Perlis, 2014)
It is an expert system to control construction problems in rigid highway pavements. It is a one of alternative it can give a help and solution to control a construction problem and also this system can save a time in the construction work and maintenance work in the future. The situation was when the contractor doing the construction, this system can be a reference to make sure that any problem can be solved faster and do not need to find in internet and journals.